Sustainability Reporting And Financial Performance: A Case Study On Indonesia’s Mining Sector - Miratul Husna Neris; Galih Mulya Subastyan; Sari Kartikaningrum; Afrida Nur Chasanah (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the effects of economic, environmental, and social disclosures on the financial performance of Indonesian mining companies. Panel data from 25 mining companies listed on the Indonesia Stock Exchange during 2021–2024 were analyzed using the Estimated Generalized Least Squares (EGLS) approach. Sustainability disclosure was measured using the GRI Standards 2016, with Return on Assets (ROA) as the financial performance proxy. A one-year lagged robustness test assessed the persistence of the observed associations.Environmental disclosure was positively associated with financial performance, whereas economic and social disclosures were negatively associated. The robustness test suggested that economic and environmental disclosure effects were primarily contemporaneous, while the negative association of social disclosure appeared to persist.The findings provide insights for firms and policymakers in improving sustainability reporting practices. This study examines the three dimensions of sustainability disclosure and incorporates a lagged robustness test to assess the persistence of the observed associations.